Different mould design for the manufacture of composite products / Mohd Jafni Hashim … [et al.] - Hashim, Mohd Jafni; Che Haron, Mohd Aminuddin; Abdul Latif, Nur Hannani; Ahmad, Junaiza; Kamarudin Zaki, Norashikin; Abdullah, Zaimatul Aqmar; Muhammed, Suhaimi (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2012)
Composite products are currently being produced by stainless steel moulds which are costly, consume space and not mobile. Alternative moulds are designed and produced from fiberglass and silicone rubber. Several advantages of these newly designed moulds include much easier fabrication, lower cost and faster speed of production. Composite products from easily available raw materials such as coconut husks, rice husks, oil palm residues and others can be manufactured using such moulds thus generating side income for the villagers leading to improve economy. Therefore the potential for commercialization is very great.